2002
DOI: 10.1080/713746657
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Heavy Metals (Zn, Cu, Pb, Cd) in Flat-Tree Oysters Isognomon Alatus Exposed to Pig Farm Effluent

Abstract: Field experiments were conducted to measure the accumulation of heavy metals (Zn, Cu, Pb, Cd) in oysters Isognomon alatus transferred from the Sepang Kecil River (clean area) to the Sepang Besar River (polluted area), for a period of 6 months. Oysters were placed in an area near an effluent from pig farm. There were increase in all metals studied in the oysters introduced to the Sepang Besar River. The metals accumulated by transplanted oysters indicated chronic pollution by metals from the pig farm effluent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 19 publications
(25 reference statements)
2
19
0
Order By: Relevance
“…In addition, the plotting of the Zn concentrations in the different geochemical fractions of the sediment with those of the byssus and ST were fitted to statistical equations including linear [ Y = a + bx ], logarithmic [ Y = a + b log x ], and exponential [ Y = a ( e bx )] equations, by using the KaleidaGraph graphical software. The curve equation which gave the highest R-values was selected [14].…”
Section: Zn Analysismentioning
confidence: 99%
“…In addition, the plotting of the Zn concentrations in the different geochemical fractions of the sediment with those of the byssus and ST were fitted to statistical equations including linear [ Y = a + bx ], logarithmic [ Y = a + b log x ], and exponential [ Y = a ( e bx )] equations, by using the KaleidaGraph graphical software. The curve equation which gave the highest R-values was selected [14].…”
Section: Zn Analysismentioning
confidence: 99%
“…Dried samples were crushed and sieved through a 0.63 mm stainless steel sieve. The aqua-regia digestion method was used according to the procedure of [23] and [24]. About 1g of ground dried sediment was digested in a 10 mL mixture (4:1) of nitric acid and perchloric acid.…”
Section: Sedimentmentioning
confidence: 99%
“…In the literature, only limited biomonitoring studies on trace metals were reported using I. alatus, except for those reported by some researchers (Campos 1988;Jaffe et al 1998;Sbriz et al 1998;Saed et al 2001Saed et al , 2004. Therefore, the objective of the present study was to determine the bioavailabilities and contamination by Fe, Ni, and Cu in the four different soft tissues (mantle plus gill, muscle, byssus, and remaining soft tissue) of I. alatus collected from seven geographical populations in the mangrove areas of Peninsular Malaysia.…”
Section: Introductionmentioning
confidence: 97%
“…In this study, the flat tree oysters Isognomon alatus (Family: Isognomonidae) was focused upon since they are potential candidates for heavy metal biomonitoring studies and they can be widely found along the mangrove estuaries of the Sepang and Lukut areas in the west coast of Peninsular Malaysia. Earlier, Saed et al (2001) studied metal concentrations in oysters after exposure to pig farm effluents, and Saed et al (2004) reported metal depuration using I. alatus under field and laboratory conditions. The above two studies indicated that I. alatus has a strong capability of accumulation and depuration of Cd, Cu, Pb, and Zn and therefore could be used as a suitable biomonitor.…”
Section: Introductionmentioning
confidence: 98%